Lipid rafts signaling detected by FRET-based molecular biosensors - Seong, Jihye (KOREAN SOC APPLIED BIOLOGICAL CHEMISTRY, 2015)
Cells recognize and process various extracellular signals via transmembrane receptors and membrane-associated signaling molecules. Therefore, the precise regulation of these signaling events at the plasma membrane, which occur spatiotemporally, is necessary for proper cellular functions such as cell proliferation, migration, and survival. The plasma membrane may contain dynamic microdomains called lipid rafts, which are suggested to be crucial for the regulation of efficient and specific signaling pathways. However, because of the limitation in methodologies, the specific molecular mechanisms underlying dynamic signaling events at lipid rafts are largely unknown. This review discusses the traditional biochemical methods for the visualization of lipid rafts and the related signaling events at these microdomains. In addition, the review reports on fluorescence resonance energy transfer (FRET)-based molecular biosensors with lipid rafts targeting sequences as a powerful tool for live-cell imaging of spatiotemporal signaling events at lipid rafts. In particular, examples of dynamic lipid rafts signaling mechanisms visualized by FRET-based biosensors in live cells are covered in the last section.
Keywords: FOCAL ADHESION KINASE; RICH MEMBRANE DOMAINS; GPI-ANCHORED PROTEINS; PLASMA-MEMBRANE; MICRODOMAINS; ACTIVATION; SRC; CHOLESTEROL; CAMP; ORGANIZATION